The Gut Microbiota of Obese Children Releases Lower Antioxidant Capacity from Food than That of Lean Children - Navajas Porras, Beatriz; Pérez-Burillo, Sergio; Hinojosa Nogueira, Daniel; Douros, Konstantinos; Pastoriza, Silvia; Rufián-Henares, José Ángel (MDPI, 2022)
The prevalence of obesity has been increasing in children over the last few decades, becoming a concern for health professionals and governments. Gut microbial community structure in obese people have been found to differ from that of lean subjects for some taxa which could result in different production of microbial metabolites. The aim of the present work was to study whether the gut microbiota from obese children extracts a different concentration of antioxidant capacity than the gut microbiota from lean children. For this purpose, different foods were in vitro digested and in vitro fermented using fecal material from obese and lean children. FRAP, DPPH and Folin-Ciocalteu methods were used to measure the antioxidant capacity released during digestion and fermentation. Overall, when using lean gut microbiota, antioxidant capacity released was higher when measured via DPPH and FRAP. Moreover, according to DPPH results, lean gut microbiota could potentially release more antioxidant power from vegetables than from animal products, while obese gut microbiota did the opposite. On the contrary, with the FRAP method obese gut microbiota released higher levels of antioxidant power from plant products than from animal products, but the final antioxidant capacity was still lower than that released by lean gut microbiota. Therefore, these results reflect that the total antioxidant capacity of foods is influenced by the gut microbiota, although whether that antioxidant capacity is released from plant or animal products can be slightly influenced by the method used for analysis.
Keywords: Obesidad en niños; Flora intestinal - Investigación; Antioxidant capacity; In vitro digestion; In vitro fermentation; Obesity; Children; Gut microbiota